Prenatally detected six duplications at Xp22.33-p11.22: a case report - Xue Zhang; Jian Li; Lan Zhang; Hongli Liu; Hong Yi; Mingxing Liang; Jianyu Luo; Junnan Li; Yanling Dong (BMC, 2023)
Abstract Background The discrepancy between the results of cytogenetics and the results of chromosome microarray analysis (CMA) has often led to confusion over genetic counselling for prenatal diagnosis. Case presentation The prenatal ultrasound results of a congenital heart defect (CHD) foetus displayed an apartial endocardial pad defect and permanently dilated coronary sinus and left superior vena cava at 21 weeks of gestation. Cytogenetic analysis, CMA, fluorescent in situ hybridization (FISH) and multiplex ligation-dependent probe amplification (MLPA) with foetal cord blood samples were used to detect the genetic aetiology. Routine G-binding cytogenetic analysis showed normal karyotypes in both the foetus' and parents' blood samples. CMA results demonstrated that there were 53.973-Mb recurrent CNVs at Xp22.33-p11.22, as confirmed by MLPA assay. Conclusions Herein, we described the CNV of six duplications at Xp22.33-p11.22 and the 53.973 Mb duplication CNV that was not found in foetal cord blood samples by conventional cytogenetic methods, and it was confirmed by CMA and MLPA. Our novel findings will provide helpful information for prenatal diagnosis and genetic counselling for foetal CHDs.